Horizons, Figures, and Machines: The Dialectic of Utopia in the Work of Fredric Jameson. - Wegner, Phillip E. (Utopian Studies, 1998)
Discusses the dialectic of Utopia in the work of Fredric Jameson. Hermeneutic approach of Jameson to the utopian horizon; Details on Jameson's original engagement with the work of Ernst Bloch; Arguments made by Jameson in his work `Marxism and Form,' in 1971.